2017
DOI: 10.3233/jvr-170872
|View full text |Cite
|
Sign up to set email alerts
|

Working with schools: What employment providers need to know for successful collaboration1

Abstract: Abstract. BACKGROUND:This APSE workshop shared one state approach to interagency collaboration for transition-age youth. The purpose of the workshop was to determine value-added by working collaboratively and share preliminary results of a school-to-work project. OBJECTIVE: Using a collaborative of employment providers embedded in schools to improve agency connections prior to leaving school and work experiences that lead to employment outcomes. METHOD: The goal of the Collaborative was to provide employment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The first theme was identified based on 36 articles (e.g., Aspel et al, 1999; Fabian et al, 2016; Fish et al, 1997; Grossi & Thomas, 2017). These articles suggested that professionals from different agencies should ensure that transition plans were easy to understand, were jointly developed for youth, and that specific responsibilities were assigned to stakeholders based on their expertise and available resources.…”
Section: Resultsmentioning
confidence: 99%
“…The first theme was identified based on 36 articles (e.g., Aspel et al, 1999; Fabian et al, 2016; Fish et al, 1997; Grossi & Thomas, 2017). These articles suggested that professionals from different agencies should ensure that transition plans were easy to understand, were jointly developed for youth, and that specific responsibilities were assigned to stakeholders based on their expertise and available resources.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, collaborations between employment providers and schools also suggested several benefits. For example, schools have information on age-appropriate transition assessments, which can be fundamental to the initiation of the Discovery process, development of work experiences, or facilitation of job development (Grossi & Thomas, 2017). Thus, career assessments are valuable towards the planning of transition services and supports for transition-age youth with disabilities, especially when strong collaborations exist among schools and employment providers.…”
Section: Outcomes From Collaborationsmentioning
confidence: 99%
“…Not only is the coordination of transition services mandated by legislation, such as IDEA of 2004, but research has also proven its relevance and positive impact on employment. Moreover, Grossi and Thomas (2017) discovered that collaborations between schools and employment providers resulted in students being more connected to VR services along with other community agencies; this resulted in transition-age youth with disabilities having more opportunities for work experiences, internships and paid employment. Thus, collaborations among school and employment providers lead to better provision of services for transition-age youth with disabilities, which can then positively impact the likelihood of them obtaining competitive employment.…”
Section: Rehabilitation Counselors and Educators Journalmentioning
confidence: 99%
See 2 more Smart Citations